PATTERNS OF PSYCHIATRIC DISORDERS IN CHILDREN AND ADOLESCENTS ATTENDING PSYCHIATRY OPD IN A TERTIARY CARE GOVERNMENT HOSPITAL IN DELHI (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Psychiatric morbidity among children and adolescents is an important public health concern because early-onset mental disorders can affect emotional development, academic performance, social functioning, and long-term adult outcomes. Clinic-based data from tertiary care centres are useful for understanding the pattern of disorders among children and adolescents who seek specialist psychiatric care.Aim: To evaluate the pattern and distribution of psychopathology among children and adolescents attending the Psychiatry Outpatient Department of a tertiary care government hospital in Delhi.Materials and Methods: This cross-sectional observational study was conducted in the Psychiatry outpatient clinic of a tertiary care government hospital over a one-year period from 11 August 2024 to 11 August 2025. A total of 612 children and adolescents below 18 years of age were included. Sociodemographic details and clinical diagnoses were collected from OPD records. Diagnoses were categorized according to ICD-10 clinical diagnostic categories. Data were analyzed using descriptive statistics.Results: The mean age of the study population was 11.53 ± 4.02 years, with an age range of 4-17 years. Males constituted 336 cases (54.9%) and females 276 cases (45.1%). Most patients belonged to the 11-17 years age group, 377 (61.6%), while 235 (38.4%) were in the 4-10 years age group. Among 609 valid diagnostic entries, intellectual disability was the most common diagnosis, 202 (33.2%), followed by conduct disorder, 69 (11.3%), attention-deficit/hyperactivity disorder, 56 (9.2%), anxiety disorder, 35 (5.7%), autism spectrum disorder, 30 (4.9%), specific learning disorder, 26 (4.3%), major depressive disorder, 23 (3.8%), and obsessive-compulsive disorder, 20 (3.3%). Neurodevelopmental disorders were more frequent in younger children, whereas conduct disorder, anxiety disorder, obsessive-compulsive disorder, bipolar affective disorder, dissociative disorder, and depressive disorders were more common among adolescents.Conclusion: Intellectual disability, conduct disorder, ADHD, anxiety disorder, and autism spectrum disorder were the leading diagnostic categories among children and adolescents attending the Psychiatry OPD. The findings highlight the need for early identification, school-based screening, parental education, and strengthening of child and adolescent mental health services in tertiary care settings.